2017
DOI: 10.1002/aenm.201700576
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Interface Optimization with Green Solvent Engineering in Mixed Perovskite Solar Cells

Abstract: Organic–inorganic hybrid halide perovskite solar cells (PSCs) have recently drawn enormous attentions due to their impressive performance (>22%) and low temperature solution processability (<150 °C). Current solution process involves application of a large amount of toxic solvents, such as chlorobenzene, which is heavily employed in both the perovskite layer and the hole transport layer (HTL) deposition. Herein, this study employs green solvent of ethyl acetate for engineering efficient perovskite and HTL laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 269 publications
(243 citation statements)
references
References 50 publications
3
234
0
Order By: Relevance
“…It is found that these solvents can help improving the quality of the Cs 2 AgBiBr 6 film due to the fast crystallization induced by anti-solvent, [43] but only IPA forms the neat and smooth film without holes ( Figure S3, S4). [45] But for all inorganic compound Cs 2 AgBiBr 6 , IPA could be suitable as anti-solvent. [44] It is found that alcohol can dissolve organic components, such as methylamine iodide and formamidine iodide, leading to decomposition of film with much rougher surface.…”
Section: High-quality Cs 2 Agbibr 6 Double Perovskite Film For Lead-fmentioning
confidence: 99%
“…It is found that these solvents can help improving the quality of the Cs 2 AgBiBr 6 film due to the fast crystallization induced by anti-solvent, [43] but only IPA forms the neat and smooth film without holes ( Figure S3, S4). [45] But for all inorganic compound Cs 2 AgBiBr 6 , IPA could be suitable as anti-solvent. [44] It is found that alcohol can dissolve organic components, such as methylamine iodide and formamidine iodide, leading to decomposition of film with much rougher surface.…”
Section: High-quality Cs 2 Agbibr 6 Double Perovskite Film For Lead-fmentioning
confidence: 99%
“…However,t he lowtemperature process normally does not produce ah ighly crystalline metal oxide. [15][16][17] For example, MgO has been deposited on the surface of the SnO 2 to passivate the defects. High-temperature annealing normally improves the crystallinity of metal oxides;however,SnO 2 ETLs cannot be sintered at temperatures above 180 8Ca sp inholes can form in the SnO 2 thin films, resultingi napoor performance of the PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Devices fabricated using the above films, exhibited record PCEs of 19.4%. Again, we should also emphasize the fact that all anti-solvents were dripped in an exactly similar manner [66]. The viability of EA as an anti-solvent was already confirmed by others [67][68][69].…”
Section: Various Anti-solvents Dripping Combined With Adduct Methodsmentioning
confidence: 52%